Biomechanical comparison between sprint start, sled pulling, and selected squat-type exercises - Okkonen, O.; Häkkinen, K. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to compare kinetics, kinematics, and muscle activity among sprint start, sled pulling, and selected squat-type exercises (countermovement jumps [CMJs] and 1/2-squats with various loads) and also to examine how these exercises correlate with the performance time of the block start (10 m). Nine male athletes (4 sprinters, 3 decathlonists, 1 long jumper, and 1 triple jumper: age = 24.9 ± 3.9 years; 100-m record = 11.35 ± 0.29 seconds; track and field training years = 11.8 ± 3.1 years) volunteered as subjects. The comparisons were made with regard to the block phase (the phase of force production toward starting blocks) of the block start. In nearly all exercises, the activity of the gluteus maximus was significantly (p < 0.05) higher than that during the block phase. Ground reaction forces were larger (p < 0.05) during the 1/2-squats and CMJs. The angular velocity of the knee was significantly (p < 0.05) higher during the CMJs than during the block phase and, in general, the kinematic values of the sled pulling and CMJs were closest to the values of the block start. The highest correlation existed between the performance time in the block start (10 m) and the takeoff velocity during the CMJ without a load (r = -0.950, p < 0.001). In conclusions, the sled pulling and CMJs can be recommended to be used in the training of the block start because both velocity and movement specificity with regard to the block start and, hence, good transfer of training adaptations to the block start can be expected.